O-011 Low-dose IL-2 Administration Expands Human Regulatory T Cells in Patients with UC and Humanized Mice and Protects Against Experimental Colitis. (February 2017) - Goettel, Jeremy; Kotlarz, Daniel; Illig, David; Canavan, James; Allegretti, Jessica; Hamilton, Matthew; Kelly, Ryan; Griffith, Alexandra; Carellas, Madeline; Nelina, Anastasia; Bousvaros, Athos; Korzenik, Joshua; et al.
Abstract : Background: Treg dysfunction or deficiency results in unopposed immune activation and autoimmunity. Interleukin-2 (IL-2) is critical for the expansion, suppressive function, and maintenance of Tregs. Although conventional T cells and NK cells respond to IL-2, Tregs are more sensitive to lower concentrations of IL-2 due to constitutive expression of CD25, the high affinity IL-2 receptor. Low-dose IL-2 therapies have shown to preferentially expand Tregs and ameliorate manifestations of graft versus host disease (Koreth et al., NEJM 2011) and HCV-associated vasculitis (Saadoun et al., NEJM 2011). Thus, low-dose IL-2 is an attractive therapeutic approach to expand Tregs in vivo for treating ulcerative colitis (UC). We utilized humanized mice to test the ability of low-dose IL-2 to expand human Tregs in vivo and ameliorate experimental colitis. Moreover, we initiated a clinical trial to evaluate whether low-dose IL-2 therapy in patients with UC could expand Tregs and ameliorate disease. Methods: To demonstrate sensitivity of human Tregs to IL-2, peripheral blood mononuclear cells (PBMCs) from UC patients were stimulated in vitro with low-dose IL-2 (10 IU/mL) and STAT5 phosphorylation was assessed by flow cytometry. For humanized mouse studies, 8-week old female NOD.Prkdcscid.Il2rg−/− (NSG) mice were administered daily intraperitoneal injections of IL-2 (Proleukin; 10k or 50k units) or PBS as a control. Two days following IL-2 injections, mice were reconstituted with 2 × 10 7 PBMCs isolated from healthy donors. To induce colitis, mice were administered a single DNBS enema on day 7 and weighed daily. Mice were euthanized on day 10 and immunophenotyping was performed on blood, spleen, and colonic lamina propria by flow cytometry while colon histology was scored on H&E stained sections. To evaluate the effect of low-dose IL-2 in patients with UC, 1 patient was enrolled under clinical trial #NCT02200445 and was administered daily subcutaneous injections of IL-2 (1.0 × 10 6 IU/m 2 ). Tregs in peripheral blood were assessed at baseline and weekly thereafter by flow cytometry. Results: In vitro stimulation of PBMCs from UC patients with low-dose IL-2 induced STAT5 phosphorylation in Tregs but not Tcons. DNBS-treated humanized mice that were administered 10k or 50k IL-2 exhibited a greater percentage of CD4 + CD25 + CD127 lo/− Tregs compared to PBS-treated controls in blood (32% and 41% versus 22%), spleen (16% and 31% versus 11%), and colon (6% and 10% versus 5%). Evaluation of colons from DNBS-treated humanized mice showed preservation of colon length in mice receiving 10k or 50k IL-2 corresponding to reduction in colitis histology scores (0.5 and 1.5 versus 2.75). The patient with UC enrolled in the low-dose IL-2 clinical trial had a baseline measurement of 2.1% CD4 + CD25 + CD127 lo/− Tregs in the peripheral blood that increased to 36.2% after 7 days and 23.7% after 14 days of low-dose IL-2 treatment. Conclusions: Our data demonstrate that humanized mice are a valuable translational research tool that validated the effects of low-dose IL-2 in expanding human Tregs in vivo and will be a useful platform in which to assess human therapeutics or drug targets prior to clinical applications. Finally, preliminary data in UC patients demonstrate that Tregs are selectively expanded by low-dose IL-2 in vitro and in vivo.